2011
DOI: 10.1136/jcp.2010.088450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human papillomavirus testing for squamous cell carcinoma of the tonsil in clinical practice

Abstract: The current study suggests that using a combination of p16 IHC/HPV ISH/HPV PCR, in a three-tiered, staged algorithm, in conjunction with consensus reporting of HPV ISH, leads to less equivocal molecular classification. In order to ensure consistent reporting of this emerging disease, it is increasingly important for the head-and-neck oncology community to define the minimum requirements for assigning a diagnosis of 'HPV-related' oropharyngeal SCC in order to inform prognosis and for stratification in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 19 publications
8
123
0
2
Order By: Relevance
“…5,13,14,18,[20][21][22] Recent studies even suggest to use 70% immunopositivity of the carcinoma tissue as a cut-off point. 4,11,12 In our study, we indeed observed the strong and block positive p16 INK4A immunostaining in all except one HPV16-positive OPSCC. Despite the fact that a small fraction of the HPV-negative OPSCC did show p16 INK4A positivity, the correlation of this surrogate marker with HPV16-presence is highly significant.…”
Section: Discussionsupporting
confidence: 78%
“…5,13,14,18,[20][21][22] Recent studies even suggest to use 70% immunopositivity of the carcinoma tissue as a cut-off point. 4,11,12 In our study, we indeed observed the strong and block positive p16 INK4A immunostaining in all except one HPV16-positive OPSCC. Despite the fact that a small fraction of the HPV-negative OPSCC did show p16 INK4A positivity, the correlation of this surrogate marker with HPV16-presence is highly significant.…”
Section: Discussionsupporting
confidence: 78%
“…There are a few different monoclonal antibody clones available for use. The most commonly utilized is clone E6H4 (MTM Laboratories; Heidelberg, Germany) [2,5,10,11], followed by other less commonly utilized clones such as 16P04 (Neo Markers; Fremont, CA) [3], and JC8 (Santa Cruz Biotechnology Inc., Santa Cruz, CA) [27]. While there has been no formal study comparing their use, studies utilizing all of these different antibodies have shown strong predictive value for their staining results [2,3,5,27].…”
Section: Technical Aspects and Practical Issues For P16 Immunohistochmentioning
confidence: 99%
“…Many advocate p16 IHC as a screening test which, when positive, is to be followed by an HPV specific test such as DNA ISH, PCR, or both [1,7,10,11]. There is an emerging view in oropharyngeal SCC, however, that the high correlation with detectable HPV RNA [9] and the strong risk stratification for patient survival provided by p16 IHC make it a suitable single marker for defining a patient's tumor as biologically and clinically favorable for treatment and counseling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations